JUDGES' CONSIDERATIONS IN DIVORCE CASES DUE TO BROKEN MARRIAGE: AN ANALYSIS OF CONTEMPORARY ISLAMIC FAMILY LAW - Ulfiana, Ana; Listyorini, Indah; Majeed, Muhamamd Yasir (al-Mawarid Jurnal Syariah dan Hukum (JSYH), 2025)
Purpose - This study aims to analyze the implementation of Supreme Court Circular Letter (SEMA) Number 1 of 2022 in divorce cases at the Yogyakarta Religious Court, especially in case Number 119/Pdt. G/2024/PA.YK using Contemporary Islamic Family Law. This regulation stipulates formal requirements for divorce, including the provision of a minimum of six months of separation from home for couples who apply for divorce on the grounds of continuous disagreement (broken marriage). This study examines the judge's reasoning in granting a divorce, even though these requirements have not been fully met.Method - Normative legal methods are used with a document study approach or literature research. This study focused on the decision of Yogyakarta Religious Court Number 119/Pdt. G/2024/PA.YK. The analysis focuses on court decisions with permanent legal force to understand the application of regulations in judicial practice by analyzing them using maqāṣid al-sharī‘ah theory and Judge Discretion theory.Findings - The results showed that even though the six-month separation requirement had not been met, the panel of judges still granted divorce because the dispute had not subsided (broken marriage), and there was no hope for reconciliation. This indicates flexibility in applying SEMA Number 1 Year 2022 following the actual conditions of the disputing couple.Research contribution/limitations - Theoretically, this study enriches the contemporary Islamic family law literature and provides insights into policies in Religious Courts. This study offers policy recommendations for applying SEMA No. 1 in 2022 to increase legal certainty in divorce cases. However, the limitation of this research is that its scope is limited to one particular case; therefore, further research with a broader scope is needed.Originality/value - The originality of this research lies in the empirical analysis of the implementation of SEMA No. 1 of 2022 in recent divorce cases, which has not been specifically studied. This study contributes to the development of contemporary Islamic legal theory and provides practical solutions for the world of justice and family law policies in Indonesia.